Hygric stresses and strategies in maintaining the association between crayfish and ectosymbiotic worms across vastly different environments - Jay A. Yoder; James A. Stoeckel; Brian S. Helms; Andre L. Lorenz; Andrew J. Jajack (Symbiosis, 2016)

Monetary discounting and ventral striatal dopamine receptor availability in nontreatment-seeking alcoholics and social drinkers - Brandon G. Oberlin; Daniel S. Albrecht; Christine M. Herring; James W. Walters; Karen L. Hile; David A. Kareken; Karmen K. Yoder (Psychopharmacology, 2015)

The Feasibility and Educational Value of Hear My Voice, a Chaplain-Led Spiritual Life Review Process for Patients with Brain Cancers and Progressive Neurologic Conditions - Katherine M. Piderman; Carmen Radecki Breitkopf; Sarah M. Jenkins; Laura A. Lovejoy; Yvette M. Dulohery; Dean V. Marek; Heidi L. Durland; Debra L. Head; Spence W. Swanson; James T. Hogg; John L. Evans; Scott E. Jorgenson; et al. (Journal of Cancer Education, 2015)

Are trends in SeaWiFS chlorophyll time-series unusual relative to historic variability - James A. Yoder; Maureen A. Kennelly; Scott C. Doney; Ivan D. Lima (Acta Oceanologica Sinica, 2010)

Climatological phytoplankton chlorophyll and sea surface temperature patterns in continental shelf and slope waters off the northeast U.S. coast - James A. Yoder; Stephanie E. Schollaert; John E. O'Reilly (Limnology and Oceanography, 2002)
Satellite‐derived chlorophyll estimates from the Sea‐viewing Wide Field‐of‐view Sensor (SeaWiFS) and Coastal Zone Color Scanner (CZCS), a large archive of in situ near‐surface chlorophyll data, and satellite sea surface temperature (SST) measurements were used to quantify spatial and seasonal variability of near‐surface chlorophyll and SST in middle shelf to slope waters off the coast of the U.S. Northeast. The results of empirical orthogonal function (EOF) analysis on normalized monthly fields (after temporal and spatial means were removed) show that all three chlorophyll climatologies have similar mode 1 temporal and spatial patterns in these waters. Mode 1, which explains about half of the total variability in monthly climatological images, shows that shelf waters in the Gulf of Maine (GOM) are out of phase with the mid‐Atlantic bight (MAB), with seasonally high chlorophyll concentrations in winter in the MAB and in summer in the GOM. The three chlorophyll climatologies begin to differ at higher modes (modes 2 and 3), although SeaWiFS and in situ climatologies keep similar features through mode 3. Higher modes in both SST and chlorophyll are related to the effects of tidal mixing on Georges Bank, differences in seasonal stratification between the southwestern and northeastern GOM, and the importance of the spring bloom in MAB outer shelf waters and western GOM. SST patterns during the CZCS and SeaWiFS eras are very similar, and this indicates that the observed differences between results obtained with these two sensors are probably not caused by differences in physical processes during the two satellite eras.

Enhanced chlorophyll at the shelfbreak of the Mid‐Atlantic Bight and Georges Bank during the spring transition - John P. Ryan; James A. Yoder; Peter C. Cornillon (Limnology and Oceanography, 1999)
In 8 yr (1979–1986) of Coastal Zone Color Scanner (CZCS) imagery, we find annual enhancement of chlorophyll at the shelfbreak of the Mid‐Atlantic Bight (MAB) and Georges Bank during the spring transition from well‐mixed to stratified conditions. Spatial and temporal extents of enhancement vary interannually, and expression is intermittent intraannually. This feature can span the entire MAB and southern flank of Georges Bank (∼1,100 km) and can be expressed for as long as 10 weeks (mid‐April to late June). Pigment concentrations within the feature average more than two times that of adjacent shelf and slope waters. Enhanced shelfbreak chlorophyll consistently coincided with the shelf‐slope front and often extended inshore of the surface outcrop of the front a few to ∼10 km. In all years except 1986, it coincided with seaward entrainment of shelf water by Gulf Stream warm‐core rings (WCRs) or meanders. Shelfbreak chlorophyll enhancement was most pronounced during 1980. Using satellite and in situ observations, we found that during 1980, it coincided with the shelf‐slope front for 10 weeks, and, unlike the spring bloom, it was dominated by the nanophytoplankton ( 10% of the variance about the mean. This annual biological feature, brought to light in satellite ocean color imagery, is an important aspect of the shelf‐slope ecology of the MAB and Georges Bank.